2022
DOI: 10.1242/dev.196220
|View full text |Cite
|
Sign up to set email alerts
|

GDF5+ chondroprogenitors derived from human pluripotent stem cells preferentially form permanent chondrocytes

Abstract: Mesodermal progeny of human pluripotent stem cells gave rise to two types of chondrogenic mesenchymal cells in culture: SOX9+ and GDF5+ cells. The fast-growing SOX9+ cells formed in vitro cartilage that expressed chondrocyte hypertrophy markers and readily underwent mineralization after ectopic transplantation. In contrast, the slowly growing GDF5+ cells derived from SOX9+ cells formed cartilage that tended to express low to no chondrocyte hypertrophy markers, while expressing PRG4, a marker of embryonic artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…Hypertrophic2 IZ transitions through Hypertrophic1 in the inferred trajectory and the former expressed genes that are upregulated during formation of anlagen or pre-hypertrophic chondrocytes in mice (BMP5, HAPLN1, ACAN and ZFHX3) 19,25 , suggesting they form the incipient cartilage template. Overall, our in vivo data are consistent with in vitro observations of the propensity for human-iPSC and mouse-ESC derived GDF5 + stromal cells to form an articular, rather than a hypertrophic phenotype 26,27 .…”
Section: Spatiotemporal Zonation Of the Incipient Synovial Jointssupporting
confidence: 88%
“…Hypertrophic2 IZ transitions through Hypertrophic1 in the inferred trajectory and the former expressed genes that are upregulated during formation of anlagen or pre-hypertrophic chondrocytes in mice (BMP5, HAPLN1, ACAN and ZFHX3) 19,25 , suggesting they form the incipient cartilage template. Overall, our in vivo data are consistent with in vitro observations of the propensity for human-iPSC and mouse-ESC derived GDF5 + stromal cells to form an articular, rather than a hypertrophic phenotype 26,27 .…”
Section: Spatiotemporal Zonation Of the Incipient Synovial Jointssupporting
confidence: 88%
“…These findings align with a recent study by Pothiawala et al, which identified a subpopulation of iPSC derivatives capable of generating and maintaining a "true" permanent-like articular cartilage phenotype that does not progress towards endochondral ossification. 39 They identified a chondroprogenitor population positive for GDF5 derived from iPSC-derived mesenchymal cells along the paraxial mesodermal lineage. Collectively, our study highlights the potential of iPSC derivatives in generating hyaline-like cartilage for the repair of joint defects.…”
Section: Discussionmentioning
confidence: 99%